Education and Skill Development for Women Empowerment A Case Study of Two NGOs in New Delhi - Sinha, Prachi; Paul , M.C. (JOURNAL OF INDIAN EDUCATION, 2019)
Education is the key to the development of an individual and the society as a whole. It helps in creating a sense of achievement and awareness in an individual’s life. Skill training is essential for acquiring new skills as well as improving existing ones. This article presents an empirical case study of two NGOs — Sulabh International and Vidya Foundation, both in New Delhi, with reference to their contribution to education and skill training of women beneficiaries. The objective of the study was to ascertain the significance of education level in skill training and women empowerment. The study showed that the education level of the beneficiaries does affect skill development, in terms of time taken to acquire the skills. The illiterate beneficiaries could also participate in the programme, but it took them a longer time to acquire the skills.The data shows that in Sulabh International and Vidya Foundation, there were illiterate and educated beneficiaries who had joined the skill training and development programme. Beneficiaries from both the NGOs had expressed their opinions on the importance of social and economic empowerment of women. As a result, the skill training programme has changed the outlook of the beneficiaries